3-D Geological modelling: a siliciclastic reservoir case study from Campos Basin, Brazil - Ulisses Miguel Correia; Alessandro Batezelli; Emilson Pereira Leite (REM: International Engineering Journal)
Abstract Reservoir static modelling plays a fundamental role in the evaluation phase of a petroleum field. Integrated modelling allows a better understanding of how the local geology and depositional systems are related through the distribution of facies and petrophysical properties within the reservoir. In this study, geological static models of the siliciclastic Carapebus Formation of Campos Basin were built using subsurface data. The applied methodology was divided into five phases: (1) establishment of a conceptual model, (2) building of a structural model, (3) generation of 100 realizations of lithofacies using sequential indicator simulation, (4) generation of 100 realizations of porosity and permeability using sequential Gaussian simulation, and (5) validation of models by targeting both statistical and geological consistency. The obtained models are consistent and honor the conditioning data. A lithofacies constraint is crucial to better characterize the petrophysical properties distribution of the reservoir. A Dykstra-Parsons coefficient of V=0.52 characterizes this reservoir as moderately homogeneous.